Characteristics of the oxides and suboxides on Zr-1.0Nb-0.01Cu isothermally oxidised in steam at 650–1200 ℃. (January 2023) - Chen, Lijun; Luan, Baifeng; Ma, Shuyu; Wan, Peng; Bai, Guanghai; Liu, Yinli; Zhang, Yanwei
Abstract: The texture of monoclinic ZrO2, grain morphology and crystal structure of suboxides ZrO and Zr3 O, and orientation relationships near the ZrO2 /α-Zr(O) interface of Zr-1.0 Nb-0.01Cu isothermally oxidised in steam at 650–1200 ℃ were investigated. The findings show that the morphology and distribution of the suboxide phase ZrO vary significantly with temperature, and both ZrO and Zr3 O grains have hexagonal structures. The number density of orientation relationships of different phases near the interface decreases as the oxidation temperature increases. The characteristics of the oxides and suboxides can provide some insights into the understanding of the high-temperature oxidation and cooling processes. Highlights: A fibre texture of the bulk m-ZrO2 oxide lies between ( 10 1 ¯ ) and ( 10 6 ¯ ) after oxidation at 650–1200 ℃. Including the interface, suboxide ZrO can also be found in the oxide film or grain/sub-grain boundary of α-Zr(O)sat. The number density of orientation relationships grain by grain near the interface varies greatly with oxidation temperature. Both ZrO and Zr3O suboxides have a hexagonal crystal structure.